The Metaphysics of Justice: Ayelala’s Rise in Benin and Other Parts of Edo State - Benson Ohihon Igboin (Yoruba Studies Review, 2021)
This article discusses the origin, spread and efficacy of the deity Ayelala, who is responsible for the execution of justice. After an account of the deification of Ayelala, it discusses the recent spread of the deity, originally from the areas inhabited by the Ijaw, Ilaje, and Ikale, to Benin, where her presence has been highly effective in combating public crimes such as theft, robbery and kidnapping. Beyond the punishment and control of public crimes, a report of Ayelala’s revelations about the causes of a personal death also illustrates the deity’s ability to provide justice in personal matters. The article argues that doubts about Ayelala’s existence, as put forward by some critics, are illogical and indeed irrelevant as long as the deity is seen to produce results. Building on the arguments of the British anthropologist E. E. Evans-Pritchard, who suggests that witchcraft explains unfortunate events, this article argues that the experience of certain fortunate events, such as the punishment of evildoers or the revelation of metaphysical causes of death, confirm the existence of Ayelala as a counter-force to witchcraft and other forms of metaphysical evil.